Implementation of the Additional Income Policy for State Civil Apparatus in the East Bolaang Mongondow Regency Government - Mokoginta, Ade Herly F; Wawointana, Thelma; Tumbel, Goinpeace (Technium Social Sciences Journal, 2025)
The purpose of this research is to find out, analyze, and describe how the implementation of Regent Regulation 5 of 2022 concerning Additional Income for State Civil Apparatus in the East Bolaang Mongondow Regency Government Environment. This research uses qualitative research methods with data collection techniques in the form of observation, interviews, and document studies. The results showed that the amendment of Regent Regulation No. 5 of 2022 to Regent Regulation No. 3 of 2024 reflects the efforts of the Regional Government of East Bolaang Mongondow Regency to improve accountability, transparency, and effectiveness of providing Additional Employee Income (TPP) to the State Civil Apparatus (ASN). Some important findings from this policy are: first, although the TPP budget has been available every year, obstacles such as delays in fund transfers and technical problems with the Regional Government Information System (SIPD) can hinder its disbursement. Second, this policy links TPP with performance indicators, discipline, and employee attendance, which aims to increase ASN productivity and professionalism. Third, employee discipline and an accurate attendance system play an important role in the smooth disbursement of TPP. Fourth, although the budget for TPP has been prepared, flexible and efficient management is still needed to overcome obstacles. Fifth, obstacles related to requirements such as Indemnity Claims (TGR) and proof of tax payment can slow down the TPP disbursement process. Finally, internal and external communication is effective but still needs improvement to increase the efficiency and accuracy of TPP disbursement.